Education, State and hegemony from Gramsci: the role of intellectuals in the democratic transition in Mexico - Ramírez , Liberio Victorino; Soto Espinoza, Yschel (Facultad de Ciencias Políticas y Sociales, 2021)
Marxism or post-Marxism and its applicability in the social, political or educational field in this article had the purpose of contributing theoretical-methodological elements to the Mexican social reality arguing temporary categories and concepts such as education, State, hegemony in addition to the role of intellectuals in the transition to Mexican democracy, explaining the new relations of the State and higher education from Gramscian thought in the six-year period 2018-2024.Approaches were developed related to governments governed by neoliberal policies in the last thirty-five years in Mexico and compared with the current regime change, concluding that the key to regime change in addition to the economic model lies in a structural reform in the context of a popular national state with legal, legitimate and transparent public policies framed by an intellectual-moral reform in the democratic transition of the six-year administration (2018-2024) in the medium and long terms.